A modulo function-based robust asymmetric variable data hiding using DCT - Khan, Sahib; Khan, Khalil; Arif, Arslan; Hassaballah, Mahmoud; Ali, Jehad; Ta, Qui Thanh Hoai; Yu, Lisu (Symmetry, 2020)
This work presents a new asymmetric data hiding technique that hides a variable number of secret message bits in the discrete cosine transform (DCT) coefficients of a cover image using a modular distance technique. Prior to data hiding, the proposed framework transforms a cover image from a spatial domain to various frequency coefficients using DCT. The DCT coefficients are arranged in two groups: one with low-frequency coefficient, and the other with the medium and high-frequency coefficients. The medium and higher frequency coefficients are processed for variable data hiding asymmetrically. The proposed technique hides variable sets of secret information bits in different coefficients. The variation in hidden secret information is maintained using a key developed based on the modulo of distance of a coefficient from the reference point. The same key is also used to retrieve the confidential information at the receiver ends. The results reveal that the presented framework does not create any visually significant distortion, and thus the hidden information does not attract the human visual system (HVS). The technique also results in high data hiding efficiency.
Keywords: Asymmetric data hiding; DCT; Hiding efficiency; Modulo function; PSNR; SSI M